2004
DOI: 10.1074/jbc.m407284200
|View full text |Cite
|
Sign up to set email alerts
|

TRAF3 Forms Heterotrimers with TRAF2 and Modulates Its Ability to Mediate NF-κB Activation

Abstract: A family of tumor necrosis factor receptor-associated factors (TRAFs 1-7) 1 functions as adaptor molecules for TNF receptor superfamily members by associating with the intracellular domain of these proteins and subsequently mediating downstream signaling events such as NF-B and AP-1 (1, 2). Biochemical approaches have revealed that TRAFs form homotypic multimers (3-6) as well as certain heterotypic multimers, such as those between TRAF1 and TRAF2 and between TRAF3 and TRAF5 (7-10).Previous reports have demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
69
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 56 publications
4
69
0
Order By: Relevance
“…Earlier studies have shown that both the Traf and the RING domains are involved in Traf3-mediated ncNFB inhibition (21,22). The Traf domain is also required for the Traf3-NIK interaction (22,25), whereas the Traf3-Traf2 interaction could not be mapped to one domain alone (36), suggesting a more complex interaction surface. This could make the Traf3-Traf2 interaction susceptible for a regulation by an internal deletion as we observe in Traf3DE8.…”
Section: Discussionmentioning
confidence: 95%
“…Earlier studies have shown that both the Traf and the RING domains are involved in Traf3-mediated ncNFB inhibition (21,22). The Traf domain is also required for the Traf3-NIK interaction (22,25), whereas the Traf3-Traf2 interaction could not be mapped to one domain alone (36), suggesting a more complex interaction surface. This could make the Traf3-Traf2 interaction susceptible for a regulation by an internal deletion as we observe in Traf3DE8.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, it has been demonstrated that TRAF3, another family member, directly associates with p40 phox and mediates CD40-induced production of ROS in B cells [25]. Moreover, He et al [26] clearly demonstrated that TRAF3 forms heterotrimers with TRAF2, which modulate TRAF2-induced NF-jB activation. This finding, together with our results showing the interaction between p47 phox , TRAF4, TRAF6, and TRIF, indicates the cytosolic NADPH oxidase complex is likely to regulate immune cell activation signaling through a novel TRAF-TRAF dimerization-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the signaling pathways of activation of CD40 in thyrocytes have not yet been examined, these can be postulated based on data from studies of activation of necrosis factor kappa B (NFkB) by transforming growth factor-beta (TGF-b) in Graves' thyrocytes, 49 as well as of CD40 signaling in other cell types. [50][51][52][53][54][55][56][57][58][59] According to our intrinsic hypothesis, CD40 ligand more readily activates CD40, overexpressed on the surface of thyrocytes in individuals harboring the CC genotype. Once activated, CD40 receptors multimerize, recruiting TNF-receptor associated factors (TRAFs) to their cytoplasmic tails.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of the initial receptor ligation, TRAFs recruit and activate kinases such as inhibitor of k-B (IkB) kinase (IKK), leading to activation of NFkB pathway. NFkB is able to turn on transcription of a number of genes including cytokines, chemokines and adhesion molecules, which could augment thyroidal inflammation [50][51][52][53][54][55][56][57][58][59] (Figure 4b). Moreover, activation of the CD40 pathway has been shown to activate anti-apoptotic pathways in several non-lympho- The intrinsic thyroidal CD40 model.…”
Section: Discussionmentioning
confidence: 99%